Structural determinants for peptide-bond formation by asparaginyl ligases - Hemu, Xinya (2021)
Asparaginyl endopeptidases (AEPs) are cysteine proteases which break Asx (Asn/Asp)-Xaa bonds in acidic conditions. Despite sharing a conserved overall structure with AEPs, certain plant enzymes such as butelase 1 act as a peptide asparaginyl ligase (PAL) and catalyze Asx-Xaa bond formation in near-neutral conditions. PALs also serve as macrocyclases in the biosynthesis of cyclic peptides. Here, we address the question of how a PAL can function as a ligase rather than a protease. Based on sequence homology of butelase 1, we identified AEPs and PALs from the cyclic peptide-producing plants Viola yedoensis (Vy) and Viola canadensis (Vc) of the Violaceae family. Using a crystal structure of a PAL obtained at 2.4-Å resolution coupled to mutagenesis studies, we discovered ligase-activity determinants flanking the S1 site, namely LAD1 and LAD2 located around the S2 and S1' sites, respectively, which modulate ligase activity by controlling the accessibility of water or amine nucleophile to the S-ester intermediate. Recombinantly expressed VyPAL1-3, predicted to be PALs, were confirmed to be ligases by functional studies. In addition, mutagenesis studies on VyPAL1-3, VyAEP1, and VcAEP supported our prediction that LAD1 and LAD2 are important for ligase activity. In particular, mutagenesis targeting LAD2 selectively enhanced the ligase activity of VyPAL3 and converted the protease VcAEP into a ligase. The definition of structural determinants required for ligation activity of the asparaginyl ligases presented here will facilitate genomic identification of PALs and engineering of AEPs into PALs.